An ethnographic study of packaging-free purchasing: designing an interactive system to support sustainable social practices. Issue 11 (2nd November 2017) - Rapp, Amon; Marino, Alessandra; Simeoni, Rossana; Cena, Federica
ABSTRACT: Consumption practices show a strong presence of crystallised social understandings, organising rules and permanent ways of acting that prevent individuals from changing towards more sustainable habits. Over the years, human–computer interaction research tried to help people engage in sustainable lifestyles promoting the health of the Earth. However, by favouring an individualistic and rationalistic approach to design, these attempts often lacked a deep understanding of how individuals are intertwined with social dynamics and organisational structures that might determine their actions. In this article, we aim at exploring novel solutions to support people's sustainable habits, by focusing on their everyday purchases. Using an ethnographic method grounded in the social practices approach, we analyse the value that individuals ascribe to activities and objects that seem already addressed to sustainable consumption: the packaging-free purchasing practices. Starting from the insights gathered from this research, and leveraging the opportunities opened by the 3D printing technology, we design an interactive system with the aim to break the old buying routines and support the reuse of containers.